Bioaccessibility and Antidiabetic Potential of xique-xique and mandacaru Fruits in a Simulated Gastrointestinal Tract Model - Fábio Fernandes de Araújo; David de Paulo Farias; Iramaia Angélica Neri-Numa; Glaucia Maria Pastore; Alexandra Christine Helena Frankland Sawaya (Foods, 2024)
This study evaluated the influence of gastrointestinal digestion on the bioaccessibility and antidiabetic potential of xique-xique (Pilosocereus gounellei) and mandacaru (Cereus jamacaru) fruits. After digestion, the content of total phenolics and flavonoids reduced by 58.3 and 73.51% in xique-xique and 48.33 and 88.43% in mandacaru. In addition, compounds such as rutin, ρ-coumaric acid, catechin and epicatechin reduced during digestion for both fruits. The antioxidant potential by the ABTS assay increased by 153.3% for xique-xique and 273.46% for mandacaru in the intestinal phase. However, using the ORAC assay, the antioxidant potential of xique-xique reduced from 255.42 to 112.17 μmol TE g−1. The capacity of xique-xique fruit to reduce α-amylase activity reduced 23.71-fold after digestion, but the potential to inhibit α-glucosidase increased 17.8-fold. The antiglycation potential reduced in both fruits after the in vitro gastrointestinal digestion. Thus, the bioaccessibility of the phenolic compounds from the fruits, as well as their functional potential, were influenced by the digestive process, as well as by the sample evaluated.